W sprawie przyszłej organizacji nadzoru makroostrożnościowego w Polsce - Fedorowicz, Magdalena (Bezpieczny Bank, 2024)
This paper analyses and conducts an assessment of the drafted bill on macroprudential supervision over the financial system in Poland. This drafted regulation contains the legal framework, aims, tasks and competencies of a new authority – Systemic Risk Board (SRB) – which will probably be responsible for creating domestic macro-prudential policy and exercising macro-prudential supervision in Poland. The SRB will be according to Art. 458 of Regulation CRR a designated authority. The main interests of the Polish legislator by developing modern macroprudential regulation should be focused on ensuring the independence of the SRB, its functional effectiveness and the collaboration with domestic micro-prudential supervision as well. In particular this collaboration will be very important by implementing, as set out in regulation CRD IV/CRR, capital buffers or systemic risk buffers into the domestic legal system. The drafted regulatory framework of the domestic macro-prudential supervision will have a significant impact on the efficiency of macro-prudential domestic policy, and therefore deserves an extensive debate and discussion on the issue.